Answer:
58
Step-by-step explanation:
You just have to replace the value of n with 4.
C(n) = 46 + 3n
C(4) = 46 + 3(4)
= 46 + 12
= 58
Answer:
Step-by-step explanation:
x + y = 7 ------------(I)
y = 7 - x ------------(II)
x + 2y = 11 --------------(III)
Substitute y = 7 - x in equation (III)
x + 2 * (7 -x) = 11
x + 2*7 - 2*x = 11
x + 14 - 2x = 11
x - 2x + 14 = 11
- x + 14 = 11
Subtract 14 from both side
-x = 11 - 14
-x = -3
Multiply both sides by (-1)
x = 3
Substitute x=3 in equation (II)
y = 7 - 3
y = 4
Answer: The height of the tree is 27f
t
Step-by-step explanation: We can set up a proportion comparing the height of each object to the length of the shadow.
h/s
h/15=18/10
Cross multiply
10.h= 18*15
10h=270
Use the multiplicative Inverse
10
h/
10
=
<em><u>270
/10
=27</u></em>
X= 28
explanation: pythagorean theorem
Answer:
C. 3(x+5)
Step-by-step explanation:
hope this helps